Factors associated with the quality of life of caregivers of children and adolescents with chronic conditions - Érika Leite da Silva Cardoso; Sérgio Ribeiro dos Santos; Yana Balduíno de Araújo; Nívea Trindade de Araújo Tiburtino Neves; João Agnaldo do Nascimento
ABSTRACT Objective To evaluate the quality of life and associated factors in caregivers of children and adolescents with chronic conditions. Method Cross-sectional study, developed with data from the Children Information System of Adolescents with Chronic Diseases. The sample consisted of 143 caregivers. Data collection took place between August and October 2018. For data analysis, chi-square statistics and Binary Logistic Regression were used. Results Through the study it was possible to identify that the variables that had impact on the low quality of life of the caregiver were: greater number of children with chronic conditions, routine use of medication, and financial limitations, which were considered risk factors. In turn, owning a home and having emotional support were protective factors. Conclusion It was observed that the caregivers had low quality of life, and knowledge of the factors that contribute to this may enable an outstanding care to the caregiver.